Effects of Seed Rate on Seed Multiplication Ratio, Seed Quality And Yield of Malt Barley Seed Classes Under Irrigated Conditions in Northwest Amhara - Wasie, Tilaye Anbes; Shibie, Belayneh (Journal of Tropical Crop Science, 2024)
Field experiments were conducted to identify seed rate enhancing seed multiplication ratio, seed quality and yield on Ibone (174/03) malt barely variety performance in Koga district during 2019 and 2020 irrigation seasons. Three seed classes (breeder, pre-basic and basic seeds) and seed rates (40, 60, 80 and 100 kg.ha-1) were compared. The experimental design randomized complete block in factorial arrangement with three replications. Analysis of variance was showed that the interaction effect of seed class and seed rate was not significant (P>0.05) for the parameters of days to maturity, plant height, spike length, seed yield, seed multiplication ratio and thousand seed weight. The study result depicted that seed rate had brought significant effect on the seed yield and multiplication ratio of malt barely. Results indicated that lower seed rates gave better seed multiplication ratio in the districts. Increasing seed rate from 40 to 80 kg.ha-1 has increased seed yield from 3356.1 kg.ha-1 to 3696.8 kg ha-1 though seed yield difference between seed rates of 60 and 80 kg.ha-1 was statistically non-significant (p>0.05). Increasing seed rate from 40 to 60 kg.ha-1 has continuously improved seed yield from 3356.1 to 3592.1 kg.ha-1 in all seed class in the districts, but the difference was statistically non-significant. In conclusion, seed rates as low as 60 kg.ha-1 can be used at all seed classes to accelerate early generation seed multiplication within the fast track variety release program in Western Amhara Region.